Analisis Faktor-Faktor yang Mempengaruhi Kepuasan Penumpang di Bandar Udara: Studi Literatur dari Perspektif Layanan, Teknologi, dan Operasional - Shabira Afina Pajri; Anisa Anastasya; Ubaedillah Ubaedillah (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze the factors influencing passenger satisfaction at airports through three main perspectives: service, technology, and operations. The background of this research is based on the increasing competition between airports in providing an optimal travel experience amidst the development of the aviation industry and the increasing passenger demands for service quality. This study uses a literature study approach by analyzing ten selected scientific journals that specifically discuss airport service quality from various perspectives. The results of the study indicate that the service perspective, specifically those encompassing SERVQUAL dimensions such as reliability, responsiveness, empathy, assurance, and tangibles, has a significant contribution in shaping the perception and satisfaction of airport service users. The technology perspective also plays a significant role, particularly through the implementation of self-services such as self-check-in, Flight Information Display Sistem (FIDS), e-gates, and digital service applications that simplify the travel process. One of the studies analyzed shows that the application of technology can contribute up to 96.8% to user satisfaction, indicating the significant role of digitalization in this industry. From the operational side, factors such as speed of service at the check-in counter, queue time management, completeness and cleanliness of public facilities, and ease of access to the terminal have an equally important influence. These findings underscore that passenger satisfaction is influenced not only by service quality at the point of direct interaction, but also by the smoothness of the overall operational flow. The study's conclusions emphasize the importance of integrating these three perspectives in strategic planning for airport service improvement.